No nap! yes nap! - Palatini, Margie (Little, Brown and Company, 2014)
"Follow Mommy on her quest to settle Baby down for a nap as Baby dashes from family room to living room, both on the table and under it, through the kitchen and even hiding in the laundry basket"--